Change — New directions for architecture and urbanism - Alkemade, Floris (International Planning History Society Proceedings, 2016)
‘The big challenge for the twenty-first century is the promotion of freedom of thought. The destructive mechanism of the crisis has ensured that exuberance, radicalism and even the longing for utopia have been demolished among architects. I believe these are precisely the qualities we now need in order to innovate.’ Interview with Floris Alkemade, the Chief Government Architect, ArchiNed, 29 March 2016. Although demands for a new, social role for architecture are growing louder, central government’s time-honoured role as a guiding force has been marginalised and new strategies are called for. Chief Government Architect Floris Alkemade presents his vision and agenda for the coming four years. Central to his talk is the search for the social element within the architecture brief and innovation through design. How can architects and planners engage with social issues such as population decline, migration, vacant buildings and an ageing population? What role does research play in this? What are the conditions under which design can have a real influence? What does this mean for the discipline?